Pengaruh Persepsi Kemudahan Penggunaan, Persepsi Manfaat dan Risiko Terhadap Minat Pengunaan E – Payment Qris - Hutahayan, Brigina; Siahay, Adolf Z. D; Muslimin, Ulfah Rizky (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2024)
This study examines the influence of perceived ease of use, perceived benefits, and risks on interest in using QRIS e-payments among Cenderawasih University students, and analyses differences in interest based on faculty and gender. The background of this study is the increasing adoption of digital payments in Indonesia, including QRIS, but there is still limited research on the factors that influence interest in use among students. The purpose of the study was to analyse the effect of the three variables on interest in using QRIS and to examine differences in interest between faculty and gender groups. The research method uses a quantitative approach with data collection techniques through questionnaires. The research sample consisted of 133 Cenderawasih University students selected using purposive sampling technique. Data analysis using Smartpls 4.0 and group difference test (Two Way Anova) with SPSS. The results showed that perceived ease of use and perceived benefits had a significant positive effect on interest in using QRIS, while risk had a significant negative effect. T-tests showed a significant difference in risk by Feb faculty, but no significant difference by gender. In conclusion, to increase interest in using QRIS among university students, service providers need to focus on increasing benefits and ease of use, and minimising risks. Keywords: Perceived ease of use, perceived benefits, risk, interest in us.